2016
DOI: 10.5424/sjar/2016141-7492
|View full text |Cite
|
Sign up to set email alerts
|

Do agrochemicals used during soybean flowering affect the visits of Apis mellifera L.?

Abstract: <p>In the Pampa region of Argentina, most beehives are situated near to soybean [<em>Glycine max </em>(L.) Merr.] crop and honey bees (<em>Apis mellifera </em>L.) use its floral resources. Soybean is often sprayed with pesticides but very little is known about their repellent action against bees. This study evaluates the visit of honey bees to crop after the application of agrochemicals aiming to check for repellency of them and estimate the possible impact on crop pollination<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
1
6
0
4
Order By: Relevance
“…Despite these results, it was found that the products Xentari and Dipel did not interfere in survival of Africanized honey bees A. mellifera (24-h old and foragers). Bacillus thuringiensis , in other tests, was also shown to be safe for A. mellifera , not causing mortality 37 and, did not change the visitation behavior of these pollinators to soybean flowers 38 or locomotor activity 39 , corroborating the results of our study, which also did find no change behavior of insects that were exposed to the bacteria. Besides that, it was observed that some isolates from B. thuringiensis do not negatively affect adult and larvae of worker bees from A. mellifera 37 , not causing sublethal effects such as the larvae development, the food consumption, and proboscis’s extension response in adults 39 .…”
Section: Discussionsupporting
confidence: 89%
“…Despite these results, it was found that the products Xentari and Dipel did not interfere in survival of Africanized honey bees A. mellifera (24-h old and foragers). Bacillus thuringiensis , in other tests, was also shown to be safe for A. mellifera , not causing mortality 37 and, did not change the visitation behavior of these pollinators to soybean flowers 38 or locomotor activity 39 , corroborating the results of our study, which also did find no change behavior of insects that were exposed to the bacteria. Besides that, it was observed that some isolates from B. thuringiensis do not negatively affect adult and larvae of worker bees from A. mellifera 37 , not causing sublethal effects such as the larvae development, the food consumption, and proboscis’s extension response in adults 39 .…”
Section: Discussionsupporting
confidence: 89%
“…Aproximadamente dos tercios de las especies apícolas abordadas en este trabajo, han sido mencionadas en estudios melisopalinológicos y entomopalinológicos llevados a cabo en el Departamento Diamante (Fagúndez & Caccavari, 2003a;Fagúndez, 2011;Fagúndez, 2015) y en la región (Fagúndez & Caccavari 2003b, 2006Caccavari & Fagúndez, 2010;Fagúndez, 2010;Fagúndez et al, 2012), poniendo de manifiesto la importancia de la flora regional como recurso apícola para Apis mellifera.…”
Section: A S P I D O S P E R M a Q U E B R A C H O -B L A N C Ounclassified
“…Important current and future RS missions and sensors to derive the status and changes of terrain and surfaces. NovaSAR-S 3 single pass InSAR S-band 2018 [410,411] GEDI LiDAR 3 LiDAR (full waveform) 3 laser transmitter, 1064 nm 2019 [45,122,123,412] ICEsat-2 3 LiDAR (full waveform) 1 laser 6 beams, 532 nm (ATLAS) 2018 [124,130,131] Sensor is used on the RS platform: UAV 1 -unmanned aerial vehicles (UAV); airborne 2 -airborne RS platform; spaceborne 3 -spaceborne RS platform. Table 7.…”
Section: Cosmo Skymedmentioning
confidence: 99%